THE PREDICTIVE ABILITY OF EARNINGS VERSUS CASH FLOW DATA TO PREDICT FUTURE CASH FLOWS: A FIRM-SPECIFIC ANALYSIS - Supriyadi Supriyadi (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 1999)
This study evaluated the value-relevance of accounting information (earnings and cash flows) in Indonesia to predict a firm’s future operating cash flows. The predictive usefulness of earnings and cash flows in association with future cash flows is of interest for three reasons. They include providing empirical evidence on the relevant accounting information to assess a firm’s future cash flows, information about the behavior and properties of Indonesian accounting information, and evidence of – or at least providing a basis for evaluating–the validity of the IndonesianAccounting Standards Committee (KPSAK) assertion on the usefulness of accounting information to assess future cash flows.The study evaluated three cash flow prediction models that employed cash flow, earnings, and a combination of earnings-cash flow variables. The models were applied on a firm-specific data set. The data used in this study were semi-annual data for the 61 sample firms (manufacturing firms)listed in the Jakarta Stock Exchange (JSX) spanning the years 1990-1997. The results of this study supported the proposed hypothesis that cash flow data provided better information to assess a firm’s future cash flows than earnings data. Since this study employed manufacturing firms only, future research is necessary to evaluate the robustness of the results to otherpopulations of firms and/or by using an alternative deflator of earnings and cash flows, such as consumer price index (CPI) or market value of the firms. Further extensions of this study include additional refinements of the prediction models on an industry-specific basis and disaggregating cash flow variables into operating, investing, and financing components in order to measure the value-relevance of the statement of cash flows.